PENINGKATAN KEMAMPUAN BIOENTREPRENEURSHIP KELOMPOK TANI MELALUI PELATIHAN BONJIKA (ABON BIJI NANGKA) - Aden Arif Gaffar Aden; Muhamad Kurnia Sugandi Andi; Iim Halimatul Mu'minah Iim; Yeni Suryaningsih Yeni; Sindi Sugiharti Sindi (BERNAS: Jurnal Pengabdian Kepada Masyarakat, 2022)
The potential in Cikedung Village, Indramayu Regency has several advantages in the delivery of the agricultural and fruit plantation sectors and the low utilization of jackfruit and jackfruit seeds in the food sector is only about 10% due to the lack of public interest in processing jackfruit seeds. This jackfruit seed shredded product "Bonjika" has not been found in many other regions so it will facilitate marketing and can compete with other food products. The implementation of community service was held from March 25-27, 2022 with the target partners of the Gerkaan Community of the Cikedung Village Farmer Group. Implementation methods using an approach include 1) Initial observation with partners about the needs and conditions of partners, 2) Initial oscillations aimed at capturing partner opportunities as study materials and, 3) Training and counseling based on Bioedupreneurship or entrepreneurship in the field of food technology 4) Partner assistance aims at the development and marketing process of processed products. The results of the training satisfaction questionnaire were obtained 72% with satisfied criteria and 28% with fairly satisfied criteria. The results of the evaluation of the activity program carried out by the PKM program implementation team by involving partners who aim to find out that it can be concluded that the entire PKM program has been implemented and applied properly.